Membangun Kemitraan Strategis melalui Pendidikan dan Kerjasama Lintas Budaya Indonesia - Thailand - Ramanata Disurya; M. Idris; Reno Fitriyanti; M. Toyib; Bz. Septeiyawan Abdullah; Rih Laksmi Utpalasari; Auzy Madona Adoma; Kiki Aryaningrum (LP2M Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2025)
This International Community Service program aims to implement strategic cross-cultural partnerships within the framework of community empowerment through education, with a focus on strengthening community capacity in Thailand. The activity was carried out by a team of lecturers and students from Universitas PGRI Palembang in collaboration with LSM SHARING at Lukmanulhakeem School, Yala, Thailand in May 2024. The implementation method used a hybrid approach (online and offline) encompassing training, workshops, interactive discussions, and academic visits. The service materials covered eight main themes: harmonization of Indonesian-Thai education policies, cultural integration, healthy food product development, economic and entrepreneurial skills, automotive engineering skills, fishery product processing, creativity development through arts and culture, and joyful learning innovation. The results showed that this international community service program successfully established effective strategic partnerships between Indonesian universities and partners in Thailand, enhanced participant capacity through the transfer of knowledge and applicable skills and strengthened cross-country academic cooperation networks. Active participation of students from various faculties enriched cross-cultural learning experiences. This activity makes a real contribution to realizing the Three Pillars of Higher Education, particularly in the aspect of international-scale community service oriented towards sustainable development and equitable welfare.